Beneficial effects of catheter ablation of frequent premature ventricular complexes on left ventricular function. Issue 10 (26th March 2014) - Zang, Minhua; Zhang, Tuo; Mao, Jialiang; Zhou, Shengheng; He, Ben
Abstract : Background: Frequent premature ventricular complexes (PVCs) are associated with a reversible form of LV dysfunction. Objective: We performed a meta-analysis to evaluate the effects of catheter ablation on improvement of LV function in patients with frequent PVCs. Methods: We searched MEDLINE for cohort studies of patients who underwent catheter ablation of frequent PVCs. LVEF both before and postablation was reported. The endpoints were changes from baseline in both LVEF and LV end-diastolic diameter (LVEDd) postablation. Quantitative analysis of continuous variables was performed according to random effect methods by MetaAnalyst Beta 3.13 software. Association between site of origin (SOO) of PVCs and degree of LVEF improvement was evaluated by meta-regression using STATA V.12.0 software. Subgroup analysis of patients with LV dysfunction at baseline was performed. Results: Fifteen studies with a total of 712 patients were included. The mean PVC burden before catheter ablation was 24% (95% CI 19% to 29%). The long-term success rate of PVC ablation ranged from 66% to 90%. The overall mean increase from baseline in LVEF postablation was 7.7% (95% CI 6.1% to 9.4%) and the overall mean decrease in LVEDd was −4.6 mm (95% CI −6.0 to −3.1 mm). Meta-regression showed no significant association of SOO of PVCs with the degree of postablation LVEF improvement. Subgroup analysis showed that the overall mean increase from baseline in LVEF postablation was 12.4% (95% CI 8.1% to 16.6%) and the overall mean decrease in LVEDd was −4.8 mm (95% CI −6.2 to −3.4 mm) in patients with LV dysfunction at baseline. Conclusions: Ablation of frequent PVCs improves cardiac function, especially for patients with LV dysfunction.